PERANCANGAN TACTILE BOOK INTERAKTIF DENGAN TEKNIK VEKTOR UNTUK LOW VISION TINGKATAN SEKOLAH DASAR - Istichomah, Intan; Ulita N, Novena (Anggada : Jurnal Desain dan Seni, 2021)
Lack of vision (low vision) is a disorder condition where the sufferer experiences a decrease in visual function, but besides that, low vision can still use some of their vision to see visually. The use of learning media for low vision is very limited. Learning media for children with visual impairments seems to be still constrained considering the inadequate reading references. This makes it difficult for them to understand the learning material. The introduction of animals around does not always have to present their physical form directly but can be through intermediary media such as books. The introduction of animals through tactile books is expected to be an alternative solution in an effort to convey information about forms and outcomes that cannot be explained only from sentences. The method used in this design is in the form of a glass box, as well as data collection through a series of activities such as observations, interviews and literature studies. The data analysis method uses SWOT to find out the opportunities that exist in the book. The design will produce a tactile book that not only presents illustrations but also includes tactile images or tactile objects. Typography in the contents of the book uses primary letters in the form of a combination of braille and the alphabet.